Relationship of Parents' Educational Capability, Availability of Learning Materials, Availability of A Learning Environment, With Homeschooling Learning Success - Isnawati, Riza; Purwito, Lasi; Ishaq, M. (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
The research provides in-depth insights into the factors influencing the success of the learning process in the context of homeschooling in Denpasar. Here are some key points that can be drawn from the findings of this research:Parental Educational Capability:Parental educational capability has a positive and significant impact on the success of homeschooling.Factors such as a lack of commitment, time, technological proficiency, motivation, and responsiveness to the child's learning problems can affect parental educational capability. The availability of learning materials has a positive effect on the success of homeschooling. Aspects such as the suitability of materials to the child's interests and talents, material flexibility, ease of provision by parents, the child's interest in the material, learning facilities from various sources, and community support affect the availability of learning materials. The availability of a conducive learning environment also contributes positively to the success of the homeschooling process. Aspects such as positive family interactions, trust in the child's interests and talents, good relationships with the child's learning environment (tutors, homeschooling institutions, tutors, and community friends), and socializing with various communities support the creation of a good learning environment. Success  The success of homeschooling is influenced by learning objectives, curriculum and teaching strategies, the teaching and learning process, and learning achievements that include the ability to have a diploma, portfolio, certificates from tutoring, and behavioral changes. Recommendations: Parents of homeschooling children are advised to pay more attention to fundamental aspects before deciding on homeschooling. If facing difficulties, it is recommended to seek assistance from learning communities or apply for scholarships from social foundations to ensure the successful implementation of homeschooling for the child.This research can serve as a foundation for parents, educators, and relevant stakeholders to enhance the quality of homeschooling in Denpasar by considering the identified factors.Keywords: Educational ability, availability of materials, environment, success in learning at homeschooling